Implikasi Hermeneutik Al Qur’an dalam Epistemologi Islam - Lailatul Maskhuroh (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2020)
Hermeneutics one of the philosophical disciplines of language, began to sound its resonance in 1998 which was first introduced by Hasan Hanafi. The pros and cons of this science still resonate with its loyal followers, and vice versa. There are professors of Islamic universities who have not recognized this knowledge from the beginning, but have not dampened the development of this science itself. So that there are those who equate hermeneutic science such as the science of interpretation and takwil. In Indonesia Aksin wijaya, Sahiron Syamsuddin, Muqsith Ghazali are lecturers who are persistent in developing this hermeneutic theory which is still productive until now. Hermeneutics is needed to understand the Koran, especially to answer contemporary problems oriented to human values ??that have not yet been resolved in classical interpretations according to Sayyid Husein Nasr. This is one of the reasons for accepting hermeneutics. There are also those who reject it and some are moderate, for example M. Quraish shihab.